2003
DOI: 10.1007/s00424-003-1172-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency fatigue is fibre type related and most pronounced after eccentric activity in rat medial gastrocnemius muscle

Abstract: Effects of fibre type composition and type of contraction on low-frequency fatigue (LFF) were investigated in isolated rat medial gastrocnemius (GM) muscle. Fast oxidative or fast glycolytic GM muscle parts of anaesthetised male Wistar rats (n=18) were activated selectively by maximal electrical stimulation of the nerve after selective cutting of sub-branches. LFF was induced by a series of 40 isometric, concentric or eccentric contractions. Post exercise (55 min), the force-frequency curves differed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 39 publications
0
31
1
Order By: Relevance
“…www.bjournal.com.br the force-pCa 2+ curve, whereas high frequencies relate to the horizontal part (25). Therefore, according to the forcefrequency relationship, little variations in intra-muscular Ca 2+ concentrations result in greater changes in the force produced with low stimulation frequencies compared to that produced with high stimulation frequencies (3,33).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…www.bjournal.com.br the force-pCa 2+ curve, whereas high frequencies relate to the horizontal part (25). Therefore, according to the forcefrequency relationship, little variations in intra-muscular Ca 2+ concentrations result in greater changes in the force produced with low stimulation frequencies compared to that produced with high stimulation frequencies (3,33).…”
Section: Discussionmentioning
confidence: 98%
“…The submaximal exercise in this study could have been accomplished with predominantly slow-twitch motor unit activation. Rijkelijkhuizen et al (25) studied regions of the rat's gastrocnemius muscle with different fiber type distribution and found greater levels of LFF in the fast glycolytic compared to the fast oxidative muscle fibers. Some investigators attribute such results to the greater susceptibility of fast contraction fibers to fatigue and injury (26,27) compared to the slow fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 It can occur as a result of concentric, eccentric, or isometric contractions. 35 However, muscle damage and delayed onset muscle soreness occur predominately with eccentric contractions. Eccentric induced soreness is generally associated with inflammatory changes in exercised muscle that includes infiltration of leukocytes, increases in lactate, increases in phosphate, fatigue, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that fast-glycolytic fibers show greater LFF than do fast-oxidative fibers (18,19). Powers and Binder (18) reported that fatigueresistant motor units from cat flexor digitorum muscles exhibited less pronounced LFF than fast intermediate and fast-fatigable motor units after electrically stimulated contractions.…”
Section: Introductionmentioning
confidence: 99%